2021
DOI: 10.3847/1538-4357/ac15f4
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Across the Magnetopause Under Radial IMF Conditions

Abstract: A global MHD model is used to study the energy transfer from solar wind to magnetosphere through magnetopause under radial interplanetary magnetic fields (IMFs). We use the streamline method to determine the smooth surface of the magnetopause by searching the inner boundary of the solar-wind streamline and discuss the roles of magnetic reconnection and viscous interaction under radial IMFs, which we compare with cases of north–south IMFs. We find that (1) the energy transfer across the magnetopause is asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 39 publications
1
16
2
Order By: Relevance
“…Our statistical results are consistent with the Figure 9 within Juusola et al (2014) for the difference in field-aligned current (FAC) during the antisunward and sunward direction of radial IMF. Lu et al (2021) have discussed that radial IMF leads to a north-south asymmetry of the magnetopause boundary layers (in simple terms, similar to Figure 7), which is responsible for the difference between sunward and antisunward IMF groups.…”
Section: Difference In Large-scale Coupling During Radial Imfsmentioning
confidence: 76%
See 3 more Smart Citations
“…Our statistical results are consistent with the Figure 9 within Juusola et al (2014) for the difference in field-aligned current (FAC) during the antisunward and sunward direction of radial IMF. Lu et al (2021) have discussed that radial IMF leads to a north-south asymmetry of the magnetopause boundary layers (in simple terms, similar to Figure 7), which is responsible for the difference between sunward and antisunward IMF groups.…”
Section: Difference In Large-scale Coupling During Radial Imfsmentioning
confidence: 76%
“…In their findings, the magnitudes of CPCP and FAC for radial IMFs are both between the corresponding magnitudes during southward and northward IMFs. Besides, Lu et al (2021) have found that the mechanical energy inputs in radial, southward, and northward IMFs are roughly comparable by the SWMF model. And the electromagnetic energy input in radial IMF is 2 times larger than that in northward IMF, but three times smaller than that in southward IMF.…”
Section: The Level Of Large-scale Coupling During Radial Imfmentioning
confidence: 76%
See 2 more Smart Citations
“…At the Earth, which has a global dipole magnetic field, it is sug- gested that under the radial IMF condition, the kinetic processes upstream of the bow shock can deflect solar wind flow, which results in the smaller strength and greater turbulence of the magnetic field in the magnetosheath, along with a weaker pressure imposed on the magnetopause (e.g., Engebretson et al 1991;Lin et al 1991;Samsonov et al 2012). The locations of the magnetopause and bow shock, and the energy transfer across the magnetopause are also influenced by the radial IMFs (e.g., Dušík et al 2010;Wang et al 2020a;Lu et al 2021). For Venus, which has no intrinsic magnetic field, but has an ionosphere and an induced magnetosphere, it is reported that by providing an additional driver, the magnetic tension pointing outward from Venus can force the magnetosheath plasma to flow faster in the azimuthal direction around Venus, while decelerating the upstream plasma in the X direction (e.g., Chang et al 2020).…”
Section: Imf Orientation Effectmentioning
confidence: 99%